Befolkningsgrupper, fundhorisonter og stiltræk i sen jernalder - Jensen, Ole Klindt (Kuml, 1964)
Population groups, association-levels of finds, and tendencies of style in the Late Iron Age As, in the Late Iron Age, the contents of the graves become gradually less and less, and compound discoveries rarer, stylistic studies become of increasing importance. These involve the noting of individual differences within standard types of objects found. However, it is necessary to bear continuously in mind regional peculiarities, as well as differences occassioned by variations in prosperity of the owners and variations in artistic originality of the craftsmen. In discoveries such as those of the Oseberg ship or the Sutton Hoo burial we can see traces of different artists, of high ability, working to the orders of rich patrons. There is reason to emphasize that we have written records of craftsmen being temporarily attached to prominent personages (1). These problems are illustrated by two contemporaneous cemeteries from the Late Iron Age which in interesting ways supplement each other. They lie only a few kilometers from each other, in Østerlarsker parish in Bornholm, and it must be assumed that the people buried there had a degree of contact with each other. Nevertheless there are definite features which differentiate the two population groups. One of the two cemeteries lies in fairly flat and fertile ploughland near Bækkegaard, and contained about 220 graves under low mounds. A little distance underneath the mound lay normally an uncremated body with its burial furnishings. Some few earlier graves contained cremation burials, with the bones laid in an urn. The majority of the burials are from about 600-900 A.D. None of the graves, not even the richer, contained ornaments of really elegant appearance, though some few of them are quite well fashioned (Fig. 3). The situation is different in the case of the other cemetery, at Lousgaard, on a prominent mount on the actual coast, with a wide view over the sea. Here there were only a little more than 50 graves, also uncremated and from about the same date. The quality of the ornaments in the richer graves is considerably above the Bækkegaard average. None, however, can have represented the highest society of the island. There are no warrior graves comparable with those of Valsgärde or Vendel, nor gold and silver ornaments suitable to an aristocracy. The most prominent grave, at Lousgaard, was of a woman with a breast-ornament set with garnets, two oval fibulae, two bracelets and beads, and with skeletons of a horse and a man besides resp. in the cairn beneath which she lay. Otherwise the normal furnishings at both cemeteries were, for the women, 2-3 fibulae, necklaces and bracelets, and, for the men, a single-edged, more rarely a double-edged, sword, a shield, spearheads, a knife, a bit, a horse and the like. It is remarkable that there is no man's grave of a richness comparable to the Lousgaard woman's. The combination of poor, fairly rich and a very few rich graves at Lousgaard suggests a manor farm with dependents, while Bækkegaard gives the impression of several more ordinary farms. Similar groupings of rich, ordinary and poor graves occur at the older and longer lasting cemetery at Slusegaard, Pedersker. Of the 1323 graves 152 were child burials, suggesting a mortality of about 40 per thousand (2). The period covered is about 600 years, from 100 B.C. to 500 A.D., giving an average of two deaths a year and suggesting a population of about 80, or about 10 families. The Bækkegaard cemetery would by the same reckoning represent a population of about 30 persons, and the Lousgaard cemetery an even smaller community. It is, of course, impossible to draw wider conclusions from this evidence, as, for example, whether communities earlier in the Iron Age consisted of extended families and later of families in the modem sense, as has been suggested. The difference between the objects from Bækkegaard and Lousgaard are presumably accounted for by greater purchasing power and better taste at Lousgaard. Among many details of decoration from both cemeteries here illustrated (and described more fully in the Danish text) mention may be made of an animal motif on a rectangular fibula from Bækkegaard grave 2, where an animal with its head turned backwards has a ribbon-formed body forming a figure-of-eight, like on the mount fig. 2. On a series of refined rectangular fibulae from Lousgaard two or more stylised ribbon-shaped animals twine in complicated interlaced patterns. An interesting rectangular fibula from Bækkegaard shows Anglo-Saxon or AngloKarolingian motifs. The decoration consists of a framework of ridges between which are figures of animals, while the open portions are filled with basketwork patterns, all motifs known from the British Isles. An interesting experiment in naturalistic reproduction is found in the animal-shaped fibulae seen from above. On a fibulae from Lousgaard grave 12 a quadruped (Fig. 4) has its legs stretched out to the sides, and each holding a snake which appears to bite the animal's head and back. While the animal is slightly stylised the snakes are reproduced completely true to nature. We have in fact here one of the earliest forms of the "gripping-beast" motif which was soon to be so popular. The background appears to be a desire on the part of the local artist to portray a situation concretely, to show a clear contact between actual living creatures, rather than an abstract artificial world of curves and twinings. But with the Viking Period Bornholm, too, passes into a time of mass production, where the inferior workshops of the new towns exploit the advantages of large turnover of poor quality goods. Ole Klindt-Jensen